Surgical treatment of newborns with critical aortic coarctation - R. Y. Lekan; V. P. Buzovskyi; I. E. Buriachenko; V. I. Bosenko; I. R. Lekan; A. V. Popsuyko; O. V. Rudomiotkin; A. I. Tomak (Ukrainian Journal of Cardiovascular Surgery, 2016)
In the period from 2004 to 2016 in the department of cardiovascular surgery Odessa Regional Pediatric Hospital were operated on 68 patients with critical CoA: 22 (32.4%) infants with isolated CoA, 16 (23%) patients CoA combined with interventricular septum defect (VSD), 31 patients (45.5%) – CoA combined with distal aortic arch hypoplasia (D?A) and other intracardiac abnormality. 66 (97%) patients underwent surgery well. Them died with 3%.